Located herbicide application to control alecrim-do-campo (vernonia nudiflora) in natural grassland (Semiárida, 2020)
To evaluate the control of alecrim-do-campo (Vernonia nudiflora) with contact herbicides, an experiment was conducted during 353 days, following a split plot block design, with three replicates in a (5x3)+1 factorial arrangement, being five herbicides in three doses and the control. The plots corresponded to the herbicides, with doses of 1.5, 3.0 and 4.5 L ha-1 of Tordon, Aminol 806, Garlon, Grazon e Plenum. The presence of V. nudiflora was evaluated prior to application and 60 and 353 days after. The application was made using a chemical applicator, which consists of a platform of adjustable height that contacts only the target plant. The herbicides did not differ in reducing the abundance of V. nudiflora and all of them reduced significantly more than the control. The chemical applicator was effective to control alecrim-do-campo, even with low herbicide concentrations, reducing the Vernonia abundance and not being harmful to the native desirable species.
Keywords: chemical control; chemical mowing; undesirable plants